2005
DOI: 10.1093/toxsci/kfi145
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chemically Induced Hepatotoxicity in Collagen Sandwiches of Rat Hepatocytes

Abstract: It has been shown that hepatocytes cultured in a collagen sandwich configuration maintain cell viability, morphology, and drug metabolizing activities for several weeks. The purpose of this study was to characterize chemically induced general toxicity in this system by exposing hepatocytes to eight different hepatotoxic compounds. Cell function and viability was measured by analyzing the secretions of urea and albumin and the release of lactate dehydrogenase. Significant decreases in urea and albumin secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In these conditions, the expression of liver specific genes, such as transporters, nuclear receptor and CYPs was stable over the whole culture duration. However, in this setting the addition of a low percentage of serum as well as the presence of EGF in the cell culture medium did not improve the cells status, despite some published evidences showing enhancement of long-term maintenance and survival of rat hepatocytes (Farkas and Tannenbaum, 2005). (Suppl.…”
Section: Discussionmentioning
confidence: 61%
“…In these conditions, the expression of liver specific genes, such as transporters, nuclear receptor and CYPs was stable over the whole culture duration. However, in this setting the addition of a low percentage of serum as well as the presence of EGF in the cell culture medium did not improve the cells status, despite some published evidences showing enhancement of long-term maintenance and survival of rat hepatocytes (Farkas and Tannenbaum, 2005). (Suppl.…”
Section: Discussionmentioning
confidence: 61%
“…Its viscosity (0.84–0.95cP at 20°C) is slightly lower than that of H 2 O (1.00cP at 20°C) even though its density is much higher. CCl 4 has also been used as co-solvent in cell culture studies [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Also unlikely is the negative effect of the selected solvents on the structural integrity of collagen as they are often used as co-solvents in biological studies [19, 20, 2326]. To further verify this, a pilot study was performed by treating demineralized bone samples (N=2) in each of the selected solvents for three days at ambient temperature and then having them tested in tension.…”
Section: Methodsmentioning
confidence: 99%
“…The idea of direct cell–cell and cell–matrix interactions promoting survival was suggested and subsequently demonstrated by reports that maintenance of differentiated phenotype in hepatocytes was enhanced by sandwiching mono-layers of cells between layers of extracellular matrix [37,38,7478]. Studies of various tumor models also long since demonstrated that maintenance of differentiated phenotype was enhanced when cells form spheroids or multi-layer cell aggregates [79,80].…”
Section: Evolving Trends In Liver Tissue Engineering In Vitromentioning
confidence: 99%